2021
DOI: 10.1038/s41593-021-00878-6
|View full text |Cite
|
Sign up to set email alerts
|

Causal role for the primate superior colliculus in the computation of evidence for perceptual decisions

Abstract: Trained monkeys performed a two-choice perceptual decision-making task in which they reported the perceived orientation of a dynamic Glass pattern, before and after unilateral, reversible, inactivation of a brainstem area involved in preparing eye movements, the superior colliculus (SC). Surprisingly, we found that unilateral SC inactivation produced significant decision biases and changes in reaction times consistent with a causal role for the primate SC in perceptual decision-making. Fitting signal detection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 65 publications
5
69
5
Order By: Relevance
“…More recently, a series of studies explored the roles of the SC and pulvinar in the processing of face and snake images [11][12][13][14][15][16][17], and concluded that the SC may be part of a fast detection network for visual threats and ecologically-relevant faces that can influence emotions [6]. Because the SC is also shown to contribute to a variety of important cognitive processes like target selection, visual attention, and perceptual decision making [18][19][20][21][22][23][24], and given that SC activity can influence cortical areas through different thalamic circuits [25][26][27][28], it stands to reason that the SC may be involved in object processing in a more general way than being specifically tuned for processing snakes and faces. In fact, experimental manipulation of SC activity is associated with altered object selectivity in a patch of the ventral visual processing stream of the cortex [29], and, similarly, the SC has a dedicated primary cortical area in mice…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a series of studies explored the roles of the SC and pulvinar in the processing of face and snake images [11][12][13][14][15][16][17], and concluded that the SC may be part of a fast detection network for visual threats and ecologically-relevant faces that can influence emotions [6]. Because the SC is also shown to contribute to a variety of important cognitive processes like target selection, visual attention, and perceptual decision making [18][19][20][21][22][23][24], and given that SC activity can influence cortical areas through different thalamic circuits [25][26][27][28], it stands to reason that the SC may be involved in object processing in a more general way than being specifically tuned for processing snakes and faces. In fact, experimental manipulation of SC activity is associated with altered object selectivity in a patch of the ventral visual processing stream of the cortex [29], and, similarly, the SC has a dedicated primary cortical area in mice…”
Section: Introductionmentioning
confidence: 99%
“…The superior colliculus (SC) is a highly laminated multisensory processing hub located in the mammalian midbrain that receives sensory input of various modalities and is involved in visual, motor, and sensory pathways ( Krauzlis et al, 2013 ; Stein and Stanford, 2013 ), as well as perceptual decision-making ( Jun et al, 2021 ). Despite studies dating back to the 1970s ( Basso and May, 2017 ), knowledge concerning the different neuronal cell types comprising SC microcircuitries and their respective functions is limited.…”
Section: Introductionmentioning
confidence: 99%
“…This argues against models in which task-relevant sensory information is directly transmitted from parietal to frontal cortex during decision formation 40,58,60 and instead highlights the importance of subcortical projection pathways via PT neurons [61][62][63] . A likely subcortical target is the SC, which receives inputs from PT neurons 18,26 and has been implicated with somatosensory 18 and visual 61,63 perception, and decision-making 38,62,64 . Parietal CStr neurons were not required for sensory perception and may thus serve a different function, such as tracking task history 65 .…”
Section: Discussionmentioning
confidence: 95%